Religião e direito: o direito no berço da religião. A separação entre direito e religião na sociedade secularizada e a permanência dos rituais religiosos no judiciário contemporâneo em geral - Bezerra, Marlene Duarte (2016)
In the broad field of law, we delimit for our research the theme of law and religion. The central question is to know whether in the rituals of the current procedural law one can find permanence, similarities and even identity with religious rituals, with special reference to the jury trials. Looking for an answer we made a historical research for anthropological and sociological works which show that law was born from religion and that they remained tied together until modern age with the separation between church, religion and state, and the secularization of society, when law acquired its autonomy in the general practice and procedure. However, despite the separation, the research seeks to demonstrate that the current judicial rituals, especially those of the jury trials in the Brazilian context, still maintain similarities and even identity with religious rituals that since the Middle Age integrated and inspired the practice of law in general and particularly the jury. To elaborate this position a field observation was made in a jury trial, with the aid of theoretical scholars that study religious ritual within the phenomenology of religion and others who support the permanence of religious rituals in the rituals of the legal process